The Interpretative Aspect in the Translations of Avot Yeshurun’s The Syrian African RiftSyrian Rift - Waldman, Omer (MiKAN, 2024)
Avot Yeshurun’s poetry poses exceptional challenges to those who attempt to translate it, beginning with its dense language, its allusions to the different registers of Hebrew, its robust lexical innovations and its deviations from standard grammar. Furthermore, significant portions of Yeshurun’s poetry are, in fact, translations of other texts, mainly from Yiddish. It is not uncommon that traces of these source languages are carried onto the Hebrew in lexicon and syntax, making the translation of Yeshurun’s work, at times, akin to a “translation of a translation.” Despite these obstacles, tens of Yeshurun’s poems have been translated into foreign languages; their translators had to confront linguistic challenges that were only sometimes comprehensive, even to Hebrew readers. Therefore, the analytical aspect of translation has gained significance as it requires that the translator demonstrate their understanding of often obscure lines and create stylistic equivalents in the target language. This article focuses on the English and French translations of poems from The Syrian African Rift (1974) — the collection whose poems were translated most often — in order to characterize the main challenges its translators had faced and interrogate the ways they interpreted ambiguous lines while attempting to maintain Yeshurun’s unique style.